A Hierarchical Analysis of 1,710 English Personality-Descriptive Adjectives. (article). - Ashton, Michael C.
The stucture of the English personality lexicon was investigated using self-ratings (N=310) on a set of 1,710 personality-trait adjectives. The 5-factor solution resembled the Big Five structure but included rotational variance of Agreeableness and Emotional Stability similar to those of other languages. In the 6-factor solution an additional factor, defined by terms such as unpretentious versus sly, resembled an Honesty-Humility factor observed in other languages . The 6-factor solution also produced an specially clear 5th factor, defined by Intellect, Imagination and Unconventionality content. The hierarchical emergence of factors from 1 to 7 was was explored, and the 7 factor solution yielded a Religiosity factor, adding to the diverse array of 7th factors observed in other languages. -- (from the author)
Keywords: Psychology-Periodicals.